Effect of habitat complexity on the distribution of Ceriodaphnia quadrangula (O. F. Müller, 1785) (Crustacea: Cladocera) in a deep lake - Adamczuk, Małgorzata (Biological Letters, 2011)
The aim of the study was to compare the density, body size, and reproduction of the cladoceran, Ceriodaphnia quadrangula (O. F. Müller, 1785), in various habitats of Lake Piaseczno (38.8 m deep) in eastern Poland. Samples were taken in the littoral zone (from emergent and submerged vegetation, as well as from open water and the surface layer of water above submerged vegetation) and in the pelagic zone (from the epilimnion, metalimnion, and hypolimnion). The results show that C. quadrangula prefers the littoral zone, as it achieves there much higher values of the analysed variables than in the pelagic zone. The number and size of adults (including ovigerous females), as well as brood size achieved equally high values in emergent and submerged vegetation, and much lower values in the other habitats (including pelagic ones). Juveniles also preferred to stay in the littoral zone but displayed clear preferences to none of the habitats.